1
$\begingroup$

I'm trying to compute the following derivative:

$$ \text{Using first principles, differentiate}: f'(x) = (x)^\frac{1}{4}\\\\ $$

I'm used to the functions being whole numbers or some simple algebra, i'm a little confused with what exactly to do when we're working with $(x)^\frac{1}{4}$.

Below is my attempt at determining $x + h$:

$$ \text{First principle formula}: f(x) = \lim_{h \to 0} \frac{f(x + h) - f (x)}{h}\\\\ \text{determine}:f(x + h)\\ f(x) = (x)^\frac{1}{4}\\\\ f(x) = (\sqrt[4]{x})\\\\ f(x + h) = (\sqrt[4]{x+h}) $$

This is where I get stuck, not sure how to determine it or substitute it into the formula and then simplify.

Any suggestions are welcomed, thanks!

$\endgroup$
  • 1
    $\begingroup$ Hint: use $p^4-q^4=(p-q)(p^3+p^2q+pq^2+q^3)$. $\endgroup$ – Yves Daoust Sep 13 '17 at 16:19
2
$\begingroup$

Note that \begin{align*} f(x + h) - f (x)&=\left(\sqrt[4]{x+h}-\sqrt[4]{x}\right)\cdot \frac{\sqrt[4]{x+h}+\sqrt[4]{x}}{\sqrt[4]{x+h}+\sqrt[4]{x}}\cdot \frac{\sqrt{x+h}+\sqrt{x}}{\sqrt{x+h}+\sqrt{x}}\\ &=\frac{\sqrt{x+h}-\sqrt{x}}{\sqrt[4]{x+h}+\sqrt[4]{x}}\cdot \frac{\sqrt{x+h}+\sqrt{x}}{\sqrt{x+h}+\sqrt{x}}\\ &=\frac{(x+h)-x}{\sqrt[4]{x+h}+\sqrt[4]{x}}\cdot \frac{1}{\sqrt{x+h}+\sqrt{x}}. \end{align*} Hence as $h\to 0$, $$\frac{f(x + h) - f (x)}{h}=\frac{1}{\sqrt[4]{x+h}+\sqrt[4]{x}}\cdot \frac{1}{\sqrt{x+h}+\sqrt{x}}\to \frac{1}{2\sqrt[4]{x}}\cdot \frac{1}{2\sqrt{x}}=\frac{1}{4x^{3/4}}.$$

$\endgroup$
  • $\begingroup$ Thanks for your response Robert. This is quite a more complicated answer than I've done myself. I think I understand the gist of it, just need to go through it to fully grasp. $\endgroup$ – Rrr Sep 13 '17 at 16:23
  • $\begingroup$ Hey Robert, I've had some time to look through your answer and was wondering if you could give me a hand understanding it. Are you able to step by step explain how you've removed the 4 sqrt in the first line and why you're multiplying it against itself over itself? Wouldn't that just be equivalent to 1 * 1. $\endgroup$ – Rrr Sep 15 '17 at 13:47
  • $\begingroup$ Here we are using two times the identity $(a-b)(a+b)=(a^2-b^2)$. For example $(\sqrt[4]{x+h}-\sqrt[4]{x})(\sqrt[4]{x+h}+\sqrt[4]{x})=\sqrt{x+h}-\sqrt{x}$. $\endgroup$ – Robert Z Sep 15 '17 at 14:14
  • $\begingroup$ Thanks Robert, I have learnt that rule, apologies for being unclear but I was more confused by the division? In your comment you wrote how I would have approached the solution but I don't put it over itself (as you have done in the comment)? $\endgroup$ – Rrr Sep 15 '17 at 14:54
0
$\begingroup$

You have the special case of $a=1$ and $b=4$ of the derivative of $x^{a/b}$, which may be found using the geometric series:

$$\frac{x^n-h^n}{x-h}=x^{n-1}+x^{n-2}h+\dots+xh^{n-2}+h^{n-1}=\sum_{k=0}^{n-1}x^{n-k-1}h^k$$

We then proceed as follows:

\begin{align}\frac d{dx}x^{a/b}&=\lim_{h\to x}\frac{x^{a/b}-h^{a/b}}{x-h}\\\\&=\lim_{h\to x}\left[\vphantom{\frac{(x^{1/b})^b-(h^{1/b})^b}{x^{1/b}-h^{1/b}}}\frac{x^{a/b}-h^{a/b}}{x^{1/b}-h^{1/b}}\right]\div\left[\frac{(x^{1/b})^b-(h^{1/b})^b}{x^{1/b}-h^{1/b}}\right]\\\\&=\lim_{h^{1/b}\to x^{1/b}}\left[\vphantom{\frac{(x^{1/b})^b-(h^{1/b})^b}{x^{1/b}-h^{1/b}}}\frac{(x^{1/b})^a-(h^{1/b})^a}{x^{1/b}-h^{1/b}}\right]\div\left[\frac{(x^{1/b})^b-(h^{1/b})^b}{x^{1/b}-h^{1/b}}\right]\\\\&=\lim_{h^{1/b}\to x^{1/b}}\frac{\sum_{k=0}^{a-1}(x^{1/b})^{a-k-1}(h^{1/b})^k}{\sum_{k=0}^{b-1}(x^{1/b})^{b-k-1}(h^{1/b})^k}\\\\&=\frac{\sum_{k=0}^{a-1}(x^{1/b})^{a-k-1}(x^{1/b})^k}{\sum_{k=0}^{b-1}(x^{1/b})^{b-k-1}(x^{1/b})^k}\\\\&=\frac{\sum_{k=0}^{a-1}x^{(a-1)/b}}{\sum_{k=0}^{b-1}x^{(b-1)/b}}\\\\&=\frac abx^{(a-b)/b}\end{align}

$\endgroup$
0
$\begingroup$

Well, a bit handwavy but:

Not for any $n > 1$, $(x^n - y^n)= (x-y)(x^{n-1} + x^{n-2}y + .... + xy^{n-2}+ y^{n-1})$

So $h = (x+h) - x = [(x+h)^{\frac 14} - x^{\frac 14}][(x+h)^{\frac 34} + (x+h)^{\frac 12}x^{\frac 14} + (x+h)^{\frac 14}x^{\frac 12} + x^{\frac 34}]$

So for $h> 0$ then $\frac {(x+h)^{\frac 14} - x^{\frac 14}}{h} =\frac 1{(x+h)^{\frac 34} + (x+h)^{\frac 12}x^{\frac 14} + (x+h)^{\frac 14}x^{\frac 12} + x^{\frac 34}}$

take limit of that.

$\lim \frac {(x+h)^{\frac 14} - x^{\frac 14}}{h} =\lim \frac 1{(x+h)^{\frac 34} + (x+h)^{\frac 12}x^{\frac 14} + (x+h)^{\frac 14}x^{\frac 12} + x^{\frac 34}}=\frac 1 {4x^{\frac 34}}=\frac 14x^{-\frac 34} $

$\endgroup$
  • $\begingroup$ I think the goal is to use the limit definition of the derivative. $\endgroup$ – Simply Beautiful Art Sep 13 '17 at 17:04
  • $\begingroup$ I think the goal is to use the limit definition of the derivative. $\endgroup$ – Simply Beautiful Art Sep 13 '17 at 17:19
  • $\begingroup$ Oh,....yeah. Okay. $\endgroup$ – fleablood Sep 13 '17 at 17:26

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.